Expedient Access to Normal‐ and Abnormal‐ N‐Heterocyclic Carbene (NHC) Magnesium Compounds from Imidazolium Salts. Issue 22 (27th September 2016) - Ghadwal, Rajendra S.; Rottschäfer, Dennis; Schürmann, Christian J.
Abstract : Treatment of imidazolium salts (IPrH)Cl (1 ) and (IPrH)I (2 ) with MeMgI leads to the formation of normal N‐heterocyclic carbene (nNHC) compounds (IPr)MgCl(I) (3 ) and (IPr)MgI2 (4 ) [IPr = 1, 3‐bis(2, 6‐diisopropylphenyl)imidazol‐2‐ylidene], respectively. By employing a similar strategy, the first magnesium compound (aIPr Ph )MgI2 (OEt2 ) (6 ) featuring an abnormal‐NHC [aIPr Ph = 1, 3‐bis(2, 6‐diisopropylphenyl)‐2‐phenyl‐imidazol‐4‐ylidene] is prepared by the treatment of a C2‐arylated imidazolium salt (IPrPh)I (5 ) with MeMgI. While the deprotonation of1 and2 can be accomplished at room temperature, an elevated temperature is required to deprotonate5 with MeMgI. This is most likely due to the higher p K a value of the C4‐H than that of the C2‐H hydrogen atom. Salt metathesis reaction of6 with KN(SiMe3 )2 cleanly leads to the formation of a magnesium amide derivative (aIPr Ph )Mg{N(SiMe3 )2 }2 (7 ). Compounds3, 4, 6, and7 were characterized by elemental analyses and NMR spectroscopic studies. The molecular structures of3, 4, and6 were determined by single‐crystal X‐ray diffraction analyses. Abstract :